Physical demands of soccer: lessons from team USA and Ghana matches in the 2010 FIFA WORLD CUP - Njororai, W. W. S. (Journal of Physical Education and Sport, 2012)
Distance covered and the intensity patterns of player movements using selected matches involving the national teams of United States of America and Ghana in the World Cup Soccer Tournament held in South Africa from June 11th to July 11th 2010. Methodology: A total of eight matches played by nine teams were used in the study. Team USA played against England, Slovenia, Algeria and Ghana. The national team of Ghana played against Germany, Australia, Serbia, USA and Uruguay. The eight matches comprised 12.5% of all matches played while the nine countries comprised 32% of all the tournament participating countries. Results: The results showed that soccer players on average covered 9.3 Kilometres to 13.476 per match. The United States of America players, on average, covered 10.76 km while those for Ghana covered 10.49km. Overall, the low activity movements dominated (84.1%), followed by high intensity (8.3%) and medium intensity (7.6%). However, the intensity patterns for United States of America`s players were 83.5%, 8.75% and 7.75% compared to the players from Ghana, who, were characterized by 85% low. 7.8% high and 7.2% low intensity movements respectively. Conclusions: It is apparent that soccer is an intermittent sport demanding high amounts of aerobic ability as well as anaerobic movements. Training must therefore target to develop both the aerobic as well as the anaerobic energy sources if players` performance is not to diminish towards the end of the matches.